Nano silicon-carbon composite negative electrode pre-lithiation material and preparation method thereof, battery and power-related equipment
Through high-temperature self-propagation reaction, silicon powder, lithium source and multiple carbon source polymers are mixed to form nano-silicon-carbon composite negative electrode prelithiated materials, solving the volume expansion problem of silicon-based materials during charging and discharging, improving cycle stability and first-time Coulomb efficiency, and suitable for high-energy density lithium-ion batteries.
Patent Information
- Application Number
- CN202510513516.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-07-25
AI Technical Summary
The existing lithium-ion battery negative electrode material, the silicon-based material, caused structural collapse and repeated SEI film rupture due to volume expansion during charging and discharging, resulting in irreversible lithium ion consumption and rapid attenuation of capacity. The existing nanoification technology or prelithiation methods have problems such as complex preparation, high cost, and uncontrollable reactions.
The high-temperature self-propagation reaction is used to mix silicon powder, lithium sources and multiple carbon source polymers. Through the coordinated regulation of multi-component polymers, the nanoification of silicon is achieved and graphene and silicon carbide are uniformly coated on the surface to form a prelithiation interface to inhibit volume expansion.
The volume expansion suppression of silicon-based anode materials during charging and discharging is achieved, cycle stability and first-time Coulomb efficiency are improved, and the low first-term efficiency and short life limitations of silicon-based anode materials are broken through, providing a reliable solution for high-energy-density lithium-ion batteries.
Smart Images

Figure CN120364674A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and particularly to a nano-silicon-carbon composite anode prelithiation material, a preparation method thereof, a battery, and an electricity-related device. Background Art
[0002] In the current field of lithium-ion battery anode materials, silicon-based materials are regarded as the core materials for next-generation high-energy density batteries due to their ultra-high theoretical specific capacity (about 4200 mA h / g, far exceeding 372 mA h / g of traditional graphite anodes) and low lithium potential (<0.5V vs Li / Li + ). However, silicon has an obvious volume expansion effect: silicon undergoes a volume change of about 400% during the process of lithium deintercalation / insertion, resulting in pulverization of the active material, collapse of the electrode structure, and repeated rupture / regeneration of the SEI film, causing irreversible consumption of lithium ions and significantly reducing the initial Coulombic efficiency (usually less than 80%). The severe volume effect continuously deteriorates the electrode-electrolyte interface, leading to rapid capacity decay (the capacity retention rate is often less than 50% after 300 cycles).
[0003] Although nanotechnology can alleviate volume expansion (such as nano-silicon particles, porous structures), the preparation process is complex (such as CVD method), the cost is high, and nano-particles are prone to agglomeration; existing chemical prelithiation (such as LiH reduction) or electrochemical prelithiation methods have problems such as uncontrollable reactions, many by-products, and harsh equipment requirements, making it difficult to balance prelithiation efficiency and material structure stability. Summary of the Invention
[0004] The purpose of the present application is to provide a nano-silicon-carbon composite anode prelithiation material, a preparation method thereof, a battery, and an electricity-related device to solve the above problems.
[0005] To achieve the above purpose, the present application adopts the following technical solutions:
[0006] A preparation method of a nano-silicon-carbon composite anode prelithiation material, comprising:
[0007] Mixing silicon powder, a lithium source, and a plurality of carbon source polymers, and then obtaining the nano-silicon-carbon composite anode prelithiation material through a high-temperature self-propagating reaction.
[0008] Preferably, the carbon source polymers include at least one of high carbon yield polymers and at least one of high adhesion polymers;
[0009] Preferably, the high carbon yield polymers include one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyfluoropropylene, polyperfluoroacrylate, polyethylene terephthalate, polybutylene terephthalate, polyvinyl chloride, and polystyrene;
[0010] Preferably, the high-adhesion polymer includes one or more of polyvinylpyrrolidone, ethylene-vinyl acetate copolymer, polypropylene, polyethylene, polycarbonate, polyethylene oxide, and polyamide;
[0011] Preferably, the mass ratio of the high-carbon-yield polymer to the high-adhesion polymer is (6-9):(1-4).
[0012] Preferably, the preparation method of the nano-silicon-carbon composite anode prelithiation material satisfies one or more of the following conditions:
[0013] (1) The silicon powder is elemental silicon with a particle size of 20 nm - 10,000 nm and a purity of not less than 99%;
[0014] (2) The silicon powder includes one or more of nano-silicon powder, micro-silicon powder, and porous silicon;
[0015] (3) The mass ratio of the silicon powder to the multiple carbon source polymers is (0.01-20.5):1.
[0016] Preferably, the preparation method of the nano-silicon-carbon composite anode prelithiation material satisfies one or more of the following conditions:
[0017] (1) The mixing method includes one or more of ultrasonic, mechanical stirring, and vibration ball milling;
[0018] (2) The solvents used for mixing include one or more of ethanol, pure water, isopropanol, ether, methyl acetate, and acetone;
[0019] (3) The mixing time is 0.1 - 36 h.
[0020] Preferably, the lithium source includes one or more of elemental lithium, lithium alloy, inorganic lithium salt, and organic lithium compound;
[0021] The mass ratio of the lithium source to the silicon powder is 0.5:1 - 10:1.
[0022] Preferably, the inorganic lithium salt includes one or more of lithium carbonate, lithium hydroxide, lithium oxide, and lithium fluoride;
[0023] The lithium alloy includes lithium aluminum alloy and / or lithium magnesium alloy, in which the lithium mass content is not less than 50%.
[0024] Preferably, the preparation method of the nano-silicon-carbon composite anode prelithiation material satisfies one or more of the following conditions:
[0025] (1) The temperature of the high-temperature self-propagating reaction is 1000 - 2800 °C;
[0026] (2) The high-temperature self-propagating reaction is carried out under vacuum conditions, inert atmosphere conditions or oxygen / carbon dioxide mixed atmosphere conditions.
[0027] The present application also provides a pre-lithiated material for a nano-silicon-carbon composite anode, which is prepared by using the preparation method of the pre-lithiated material for the nano-silicon-carbon composite anode.
[0028] The present application also provides a battery, including the pre-lithiated material for the nano-silicon-carbon composite anode.
[0029] The present application also provides an electricity-related device, including the battery.
[0030] Compared with the prior art, the beneficial effects of the present application include:
[0031] The preparation method of the pre-lithiated material for the nano-silicon-carbon composite anode provided by the present application completes the following processes in one step during the high-temperature self-propagating reaction: designing the nano-composite structure of silicon through the pyrolysis of various carbon source polymers, realizing the nano-sizing of silicon and enabling silicon to be uniformly coated with graphene and silicon carbide on the surface, and finally obtaining silicon with graphene and silicon carbide uniformly coated on the surface. The silicon-based anode of this structure greatly inhibits the volume expansion of silicon during charge and discharge. Through the high-temperature self-propagating reaction of the lithium source and the silicon-carbon composite, silicon-carbon composite and pre-lithiation are achieved in one step. During the reaction process, the lithium source rapidly releases active lithium at high temperature and undergoes an in-situ reaction with silicon and the cracked carbon layer to form a uniform pre-lithiated interface.
[0032] The pre-lithiated material for the nano-silicon-carbon composite anode provided by the present application greatly inhibits the volume expansion of silicon during charge and discharge. Therefore, this material has good cycle stability and high first Coulomb efficiency while having a high theoretical specific capacity. It breaks through the technical barriers of low first efficiency and short life of silicon-based anode materials and provides a reliable solution for high-energy-density lithium-ion batteries.
[0033] The battery and the electricity-related device provided by the present application have excellent electrical performance. Description of the Drawings
[0034] To more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings required for the embodiments. It should be understood that the following drawings only show some embodiments of the present application and should not be regarded as limiting the scope of the present application.
[0035] Figure 1 The cycling curve of the pre-lithiated silicon-based anode material prepared in Example 3 for 300 cycles;
[0036] Figure 2 The SEM photograph of the pre-lithiated silicon-based anode material prepared in Example 3;
[0037] Figure 3 XRD pattern of the silicon-based anode prelithiation material prepared in Example 3 Detailed implementation manners
[0038] To better illustrate the technical solutions provided in this application, before the examples, a general statement of the technical solutions is given as follows:
[0039] A preparation method of a nano-silicon-carbon composite anode prelithiation material, comprising:
[0040] Mixing silicon powder, a lithium source and various carbon source polymers, and then obtaining the nano-silicon-carbon composite anode prelithiation material through a high-temperature self-propagating reaction.
[0041] In an optional implementation manner, the carbon source polymer includes at least one of high carbon yield polymers and at least one of high adhesion polymers;
[0042] In an optional implementation manner, the high carbon yield polymers include one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyfluoropropylene, polyperfluoroacrylate, polyethylene terephthalate, polybutylene terephthalate;
[0043] In an optional implementation manner, the high adhesion polymers include one or more of polyvinylpyrrolidone, ethylene-vinyl acetate copolymer, polypropylene, polyethylene, polycarbonate;
[0044] In an optional implementation manner, the mass ratio of the high carbon yield polymers to the high adhesion polymers is (6 - 9):(1 - 4).
[0045] Using the high carbon yield material as the main component and the high adhesion material as the auxiliary component, the interface properties of the material are synergistically regulated by multi-component polymers to enhance the stability of the SEI film, thereby ensuring that the cracked carbon layer has both conductivity and mechanical strength.
[0046] Optionally, the mass ratio of the high carbon yield polymers to the high adhesion polymers can be 6:4, 7:3, 8:2, 9:1 or any value between (6 - 9):(1 - 4).
[0047] In an optional implementation manner, the preparation method of the nano-silicon-carbon composite anode prelithiation material satisfies one or more of the following conditions:
[0048] (1) The silicon powder is elemental silicon with a particle size of 20 nm - 10,000 nm and a purity of not less than 99%;
[0049] Optionally, the particle size of the silicon powder can be 20 nm, 50 nm, 100 nm, 500 nm, 1000 nm, 5000 nm, 10000 nm, or any value between 20 nm and 10000 nm;
[0050] (2) The silicon powder includes one or more of nano-silicon powder, micro-silicon powder, and porous silicon;
[0051] (3) The mass ratio of the silicon powder to the multiple carbon source polymers is (0.01 - 20.5):1.
[0052] Optionally, the mass ratio of the silicon powder to the multiple carbon source polymers can be 0.01:1, 0.05:1, 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1, 20.5:1, or any value between (0.01 - 20.5):1.
[0053] In an optional embodiment, the preparation method of the nano-silicon-carbon composite negative electrode prelithiation material satisfies one or more of the following conditions:
[0054] (1) The mixing method includes one or more of ultrasonic, mechanical stirring, and vibration ball milling;
[0055] (2) The solvents used for mixing include one or more of ethanol, pure water, isopropanol, ether, methyl acetate, and acetone;
[0056] (3) The mixing time is 0.1 - 36 h.
[0057] Optionally, the mixing time can be 0.1 h, 0.5 h, 1 h, 2 h, 6 h, 12 h, 24 h, 36 h, or any value between 0.1 - 36 h.
[0058] In an optional embodiment, the lithium source includes one or more of elemental lithium, lithium alloy, inorganic lithium salt, and organic lithium compound;
[0059] The mass ratio of the lithium source to the silicon powder is 0.5:1 - 10:1.
[0060] Optionally, the mass ratio of the lithium source to the silicon powder can be 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or any value between 0.5:1 - 10:1.
[0061] In an optional embodiment, the inorganic lithium salt includes one or more of lithium carbonate, lithium hydroxide, lithium oxide, and lithium fluoride;
[0062] The lithium alloy includes lithium aluminum alloy and / or lithium magnesium alloy, wherein the mass content of lithium is not less than 50%.
[0063] In an alternative embodiment, the method for preparing the nano-silicon-carbon composite anode prelithiation material satisfies one or more of the following conditions:
[0064] (1) The temperature of the high-temperature self-propagating reaction is 1000 - 2800 °C;
[0065] Optionally, the temperature of the high-temperature self-propagating reaction can be 1000 °C, 1500 °C, 2000 °C, 2500 °C, 2800 °C, or any value between 1000 - 2800 °C;
[0066] (2) The high-temperature self-propagating reaction is carried out under vacuum conditions, inert atmosphere conditions, or oxygen / carbon dioxide mixed atmosphere conditions.
[0067] Elemental lithium can be selected as metallic lithium in physical forms such as lithium flakes, lithium powders, lithium foils, lithium tapes, etc. The reaction environment of the lithium alloy and elemental lithium requires an inert gas (such as argon, nitrogen) or vacuum protection; inorganic lithium salts such as lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium oxide (Li2O), lithium fluoride (LiF), etc. are suitable for the oxygen / carbon dioxide mixed atmosphere.
[0068] This application also provides a nano-silicon-carbon composite anode prelithiation material prepared by using the method for preparing the nano-silicon-carbon composite anode prelithiation material described above.
[0069] This application also provides a battery including the nano-silicon-carbon composite anode prelithiation material described above.
[0070] This application also provides an electricity-related device including the battery described above.
[0071] The electricity-related device referred to in this application means a device that directly includes the above battery or is powered by the above battery, such as daily consumer goods like electric vehicles, electric bicycles, electronic watches, computers, etc., and energy storage devices, etc.
[0072] Next, the implementation solutions of this application will be described in detail with reference to specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate this application and should not be regarded as limiting the scope of this application. For those not specified in the examples, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. For reagents or instruments not specified by the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0073] Example 1
[0074] This example provides a nano-silicon-carbon composite anode prelithiation material, and its preparation method includes the following steps:
[0075] Mix polytetrafluoroethylene, polycarbonate, and polyvinylidene fluoride evenly at a mass ratio of 6:3:1 to obtain mixture A. Add silicon powder (particle size 20 - 50 nm) and mixture A to ethanol at a mass ratio of 8:1 and ultrasonically disperse for 1 hour. After pressure filtration, obtain product B. Place product B in an argon atmosphere and conduct a high-temperature self-propagating reaction with lithium flakes (mass ratio of lithium source to silicon powder is 3.5:1) at 2000 °C for 3 hours to finally obtain a pre-lithiated nano-silicon-carbon composite anode material.
[0076] Example 2
[0077] This example provides a pre-lithiated nano-silicon-carbon composite anode material, and its preparation method includes the following steps:
[0078] Mix polyperfluoroacrylate, polyvinylpyrrolidone, and polyethylene terephthalate at a mass ratio of 7:2:1 to prepare mixture A. Add silicon powder (particle size 1 - 2 μm) and mixture A to pure water at a mass ratio of 0.5:1 and mechanically stir for 6 hours. After centrifugal separation, obtain product B. React product B with lithium powder (mass ratio of lithium source to silicon powder is 5:1) in a nitrogen / oxygen mixed atmosphere (volume ratio 4:1) at 1500 °C for 2 hours to finally obtain a pre-lithiated nano-silicon-based anode material.
[0079] Example 3
[0080] This example provides a pre-lithiated nano-silicon-carbon composite anode material, and its preparation method includes the following steps:
[0081] Mix polyvinylidene fluoride, polypropylene, and polybutylene terephthalate at a mass ratio of 5:3:2 to form mixture A. Add silicon powder (particle size 5 - 8 μm) and mixture A to isopropanol at a mass ratio of 15:1 and vibratory ball mill for 0.5 hour to obtain product B. React product B with a lithium-magnesium alloy (mass ratio of lithium source to silicon powder is 8.2:1, where the mass fraction of lithium in the lithium-magnesium alloy is 60%) in a vacuum environment at 1800 °C for 4 hours to finally obtain a pre-lithiated nano-silicon-based anode material.
[0082] Example 4
[0083] This example provides a pre-lithiated nano-silicon-carbon composite anode material, and its preparation method includes the following steps:
[0084] Mix polyethylene terephthalate, ethylene-vinyl acetate copolymer, and polytetrafluoroethylene at a mass ratio of 6:2:2 to form mixture A. Add silicon powder (particle size 10 μm) and mixture A to diethyl ether at a mass ratio of 20:1 and ultrasonically disperse for 24 hours. After pressure filtration, obtain product B. React product B with lithium fluoride (mass ratio of lithium source to silicon powder is 4.8:1) in a carbon dioxide atmosphere at 2800 °C for 1 hour to finally obtain a pre-lithiated nano-silicon-based anode material.
[0085] Example 5
[0086] This example provides a pre-lithiated material for a nano-silicon-carbon composite anode, and its preparation method includes the following steps:
[0087] Mix polybutylene terephthalate, polypropylene, and polyfluoropropylene in a mass ratio of 8:1:1 to obtain mixture A. Add silicon powder (particle size 30 nm) and mixture A to acetone in a mass ratio of 0.1:1 and mechanically stir for 12 hours. After centrifugal separation, product B is obtained. React product B with lithium oxide (the mass ratio of the lithium source to the silicon powder is 2.5:1) in a helium atmosphere at 1200 °C for 5 hours to finally obtain the pre-lithiated material for the nano-silicon-based anode.
[0088] Example 6
[0089] This example provides a pre-lithiated material for a nano-silicon-carbon composite anode, and its preparation method includes the following steps:
[0090] Mix polyfluoropropylene, polycarbonate, and polyperfluoroacrylate in a mass ratio of 7:2:1 to form mixture A. Add silicon powder (particle size 200 nm) and mixture A to methyl acetate in a mass ratio of 2:1 and ultrasonicate for 8 hours. After pressure filtration, product B is obtained. React product B with lithium carbonate (the mass ratio of the lithium source to the silicon powder is 7:1) in an air atmosphere at 2200 °C for 2.5 hours to finally obtain the pre-lithiated material for the nano-silicon-based anode.
[0091] Example 7
[0092] This example provides a pre-lithiated material for a nano-silicon-carbon composite anode, and its preparation method includes the following steps:
[0093] Mix polyperfluoroacrylate, polyethylene, and polytetrafluoroethylene in a mass ratio of 6:3:1 to prepare mixture A. Add silicon powder (particle size 3 - 5 μm) and mixture A in a mass ratio of 12:1 and perform solvent-free dry ball milling for 0.1 hour to obtain product B. React product B with a lithium-aluminum alloy (the mass ratio of the lithium source to the silicon powder is 9.5:1, and the mass fraction of lithium in the lithium-aluminum alloy is 55%) in an argon / oxygen mixed atmosphere (3:1) at 2500 °C for 3 hours to finally obtain the pre-lithiated material for the nano-silicon-based anode.
[0094] Comparative Example 1
[0095] Use polytetrafluoroethylene as the sole carbon source. Add silicon powder (particle size 20 - 50 nm) and polytetrafluoroethylene to ethanol in a mass ratio of 8:1 and ultrasonically disperse for 1 hour. After pressure filtration, product B is obtained. Place product B in an argon atmosphere and perform a high-temperature self-propagating reaction with a lithium sheet (the mass ratio of the lithium source to the silicon powder is 3.5:1) at 2000 °C for 3 hours.
[0096] Comparative Example 2
[0097] Using polypropylene (a highly adhesive polymer) as the sole carbon source, silicon powder (particle size 1 - 2 μm) and polypropylene were added to pure water at a mass ratio of 0.5:1 and mechanically stirred for 6 hours, and then product B was obtained by centrifugal separation. Product B was reacted with lithium powder (the mass ratio of the lithium source to the silicon powder was 5:1) in a nitrogen / oxygen mixed atmosphere (volume ratio 4:1) at 1500 °C for 2 hours.
[0098] Comparative Example 3
[0099] Polytetrafluoroethylene and polycarbonate were mixed at a mass ratio of 6:3 to obtain mixture A. Silicon powder (particle size 200 - 300 nm) and mixture A were added to ethanol at a mass ratio of 8:1 and ultrasonically dispersed for 1 hour, and then product B was obtained after pressure filtration. Product B was placed in an argon atmosphere, without adding a lithium source, and subjected to a high-temperature self-propagating reaction at 2000 °C for 3 hours.
[0100] Comparative Example 4
[0101] Polytetrafluoroethylene and polycarbonate were mixed at a mass ratio of 6:3 to obtain mixture A. Silicon powder (particle size 20 - 50 nm) and mixture A were added to ethanol at a mass ratio of 8:1 and ultrasonically dispersed for 1 hour, and then product B was obtained after pressure filtration. Product B and lithium foil (the mass ratio of the lithium source to the silicon powder was 3.5:1) were subjected to a high-temperature self-propagating reaction at 500 °C (far lower than the range of 1000 - 2800 °C in this application) for 3 hours.
[0102] Electrochemical performance test
[0103] Using the silicon-based anode materials prepared in the above Examples 1 - 7 and Comparative Examples 1 - X as the active material, copper foil as the current collector, the active material, Super P Li, and binder were made into the anode electrode sheet at a mass ratio of 8:1:1, and a coin-type half-cell was assembled with metallic lithium as the counter electrode.
[0104] The results of the electrochemical performance test are shown in Table 1.
[0105] Table 1 Electrochemical performance data
[0106]
[0107]
[0108] Figure 1 The cycling curve of the prelithiated silicon-based anode material prepared in Example 3 for 300 cycles shows that the specific capacity decay is very slow, proving that the volume expansion of silicon is greatly alleviated.
[0109] Figure 2 The SEM characterization of the prelithiated silicon-based anode material prepared in Example 3 shows that its morphology is spherical particles with a size less than 100 nm.
[0110] Figure 3 XRD test results of the pre-lithiated silicon-based anode material prepared in Example 3, the components of which mainly include graphene, Si, LiF, and Li (1-x) Si x and SiC, etc. The XRD results confirm that a multiphase composite structure of "graphene and silicon carbide-coated silicon-lithium alloy / lithium fluoride" has been successfully constructed through high-temperature self-propagating reaction, which has both high capacity, high initial efficiency and long cycle stability.
[0111] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present application, rather than limiting them; although the present application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A preparation method of a pre-lithiated material for a nano-silicon-carbon composite anode, characterized in that, Comprising: Mixing silicon powder, a lithium source and a plurality of carbon source polymers, and then obtaining the nano-silicon-carbon composite anode prelithiated material through a high-temperature self-propagating reaction.
2. The preparation method of the pre-lithiated material of the nano-silicon-carbon composite negative electrode according to claim 1, wherein, The carbon source polymers include at least one of high carbon yield polymers and at least one of high adhesiveness polymers; Preferably, the high carbon yield polymers include one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyfluoropropylene, polyperfluoroacrylate, polyethylene terephthalate, polybutylene terephthalate, polyvinyl chloride, polystyrene; Preferably, the high adhesiveness polymers include one or more of polyvinylpyrrolidone, ethylene-vinyl acetate copolymer, polypropylene, polyethylene, polycarbonate, polyethylene oxide, polyamide; Preferably, the mass ratio of the high carbon yield polymers to the high adhesiveness polymers is (6-9):(1-4).
3. The preparation method of the pre-lithiated material of the nano-silicon-carbon composite negative electrode according to claim 1, wherein, Meeting one or more of the following conditions: (1) The silicon powder is elemental silicon with a particle size of 20 nm - 10000 nm and a purity of not less than 99%; (2) The silicon powder includes one or more of nano-silicon powder, micro-silicon powder and porous silicon; (3) The mass ratio of the silicon powder to the plurality of carbon source polymers is (0.01-20.5):
1.
4. The preparation method of the pre-lithiated material of the nano-silicon-carbon composite negative electrode according to claim 1, wherein, Meeting one or more of the following conditions: (1) The mixing method includes one or more of ultrasonic, mechanical stirring, vibration ball milling; (2) The solvent used for mixing includes one or more of ethanol, pure water, isopropanol, ether, methyl acetate, acetone; (3) The mixing time is 0.1-36 h.
5. The preparation method of the pre-lithiated material of the nano-silicon-carbon composite negative electrode according to claim 1, wherein, The lithium source includes one or more of elemental lithium, lithium alloy, inorganic lithium salt, organic lithium compound; The mass ratio of the lithium source to the silicon powder is 0.5:1 - 10:
1.
6. The preparation method of the nano-silicon-carbon composite anode pre-lithiated material according to claim 5, wherein, The inorganic lithium salt includes one or more of lithium carbonate, lithium hydroxide, lithium oxide, lithium fluoride; The lithium alloy includes lithium aluminum alloy and / or lithium magnesium alloy, wherein the lithium mass content is not less than 50%.
7. The preparation method of the nano-silicon-carbon composite anode pre-lithiated material according to claim 1, wherein, Meeting one or more of the following conditions: (1) The temperature of the high-temperature self-propagating reaction is 1000-2800 °C; (2) The high-temperature self-propagating reaction is carried out under vacuum conditions, inert atmosphere conditions or oxygen / carbon dioxide mixed atmosphere conditions.
8. A pre-lithiated material for a nano-silicon-carbon composite negative electrode, characterized in that, Prepared by using the preparation method of the nano-silicon-carbon composite anode prelithiated material according to any one of claims 1-7.
9. A battery, characterized in that, Comprising the nano-silicon-carbon composite anode prelithiated material according to claim 8.
10. An electricity-related device, characterized in that, Comprising the battery according to claim 9.
Citation Information
Cited By
Si-coated SiC-coated EG ternary composite material as well as preparation method and application thereof
CN121439760A